Priorities of Municipal Policy Makers in Relation to Physical Activity and the Built Environment: A Latent Class Analysis. Issue 3 (May 2016) - Wang, Monica L.; Goins, Karin Valentine; Anatchkova, Milena; Brownson, Ross C.; Evenson, Kelly; Maddock, Jay; Clausen, Kristian E.; Lemon, Stephenie C.
Abstract : Objective: To examine policy makers' public policy priorities related to physical activity and the built environment, identify classes of policy makers based on priorities using latent class analysis, and assess factors associated with class membership. Design: Cross-sectional survey data from municipal officials in 94 cities and towns across 6 US states were analyzed. Participants: Participants (N = 423) were elected or appointed municipal officials spanning public health, planning, transportation/public works, community and economic development, parks and recreation, and city management. Main Outcome Measures: Participants rated the importance of 11 policy areas (public health, physical activity, obesity, economic development, livability, climate change, air quality, natural resource conservation, traffic congestion, traffic safety, and needs of vulnerable populations) in their daily job responsibilities. Latent class analysis was used to determine response patterns and identify distinct classes based on officials' priorities. Logistic regression models assessed participant characteristics associated with class membership. Results: Four classes of officials based on policy priorities emerged: (1) economic development and livability; (2) economic development and traffic concerns; (3) public health; and (4) general (all policy areas rated as highly important). Compared with class 4, officials in classes 1 and 3 were more likely to have a graduate degree, officials in class 2 were less likely to be in a public health job/department, and officials in class 3 were more likely to be in a public health job/department. Conclusions: Findings can guide public health professionals in framing discussions with policy makers to maximize physical activity potential of public policy initiatives, particularly economic development. Abstract : This article provides a latent class analysis of priorities of municipal policy makers in relation to physical activity and the built environment.